Engineering spin and antiferromagnetic resonances to realize an efficient direction-multiplexed visible meta-hologram. Issue 1 (21st August 2019) - Ansari, Muhammad Afnan; Kim, Inki; Rukhlenko, Ivan D.; Zubair, Muhammad; Yerci, Selcuk; Tauqeer, Tauseef; Mehmood, Muhammad Qasim; Rho, Junsuk
Abstract : A direction-multiplexed visible metahologram is proposed. We demonstrate monolayer direction-controlled multiplexing of a transmission type metasurface hologram made of hydrogenated amorphous silicon in the visible domain. Abstract : Driven by the need for enhanced integrated performance and rapid development of ultrathin multitasked optical devices, this paper experimentally demonstrates monolayer direction-controlled multiplexing of a transmissive meta-hologram in the visible domain. The directional sensitivity is designed by imparting direction-controlled spin-dependent holographic recordings in the monolayer structure. The designed metasurface hologram consists of nano half-waveplates (HWPs) of low loss hydrogenated amorphous silicon (a-Si:H). These nano-featured HWPs are carefully designed and optimized for circularly polarized (CP) illumination to not only excite electric and magnetic resonances simultaneously but also to excite antiferromagnetic modes to ensure high transmission for the cross CP-light. The antiferromagnetic modes are excited in such a way that the transmitted CP-light maintains the E x component of the incident CP-light through even antiparallel magnetic dipoles while they reverse the E y component via odd antiparallel magnetic dipoles. As compared to the standard amorphous silicon, our a-Si:H exhibits a much lower absorption coefficient in the visible domain. The proposed single-layer design is an advanced step towards scalability, low-cost fabrication, and on-chip implementation of novel metasurfaces with substantially higher performance in the visible domain.